The Ehrhart volume conjecture is false in sufficiently higher dimensions in $\mathbb{R}^n$ : The Ehrhart volume conjecture - Agama, Theophilus (My University, 2022)
Using the method of compression, we show that volume Vol(K) of a ball K in R^2 with a single lattice point in it’s interior as center of mass satisfies the lower bound... #find the complete abstract in the attached file
Keywords: volume; ball; lattice; point